The Influence of Teamwork in the Implementation of Total Quality Management (TQM) on Customer Satisfaction - Aryoga Samudra Asmara; Meilinda Laurensia Febrihianto; Nunki Aprillita; Mira Veranita (Yayasan Adra Karima Hubbi, 2023)
Total Quality Management (TQM) is one of strategies that used to raise the caliber of healthcare services and customer satisfaction nowadays. Teamwork is the primary metric for TQM implementation. The major goals of this study are to examine current research on TQM teamwork in hospital health services and to determine how TQM teamwork is used. In this study, recent scientific articles that published between 2018 until 2023 were systematically summarized using inclusion and exclusion criteria. The conclusion of this journal article shows that teamwork is a crucial element of TQM since a strong team may boost independence, communication, and self-assurance while successfully attaining shared objectives.